Molecular Taxonomy of Sporadic Amyotrophic Lateral Sclerosis Using Disease-Associated Genes - Morello, Giovanna; Spampinato, Antonio Gianmaria; Cavallaro, Sebastiano (Frontiers in Neurology, 2017)
Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by selective loss of upper and lower motor neurons. Despite intensive research, the origin and progression of ALS remain largely unknown, suggesting that the traditional clinical diagnosis and treatment strategies might not be adequate to completely capture the molecular complexity underlying the disease. In our previous work, comprehensive genomic profiling of 41 motor cortex samples enabled to discriminate control from sporadic ALS patients and segregated these latter in two distinct subgroups, each associated with different deregulated genes and pathways. Interestingly, some deregulated genes in sporadic ALS were previously associated to familiar ALS, indicating shared pathogenic mechanisms between the two forms of the disease. In the present study, we performed cluster analysis on the same whole-genome expression profiles using a restricted (203) subset of genes extensively implicated in monogenic forms of ALS. Surprisingly, this short and unbiased gene list was sufficiently representative to allow the accurate separation of SALS patients from controls and the stratification of SALS patients into two molecularly distinct subgroups. Overall, our findings support the existence of a molecular taxonomy for ALS and represent a further step towards the establishment of a molecular-based diagnosis and patient-tailored therapies.